Evaluating Opicapone as Add-on Treatment to Levodopa/DDCI in Patients with Parkinson’s Disease - Jost WH (Neuropsychiatric Disease and Treatment, 2022)
Wolfgang H Jost Parkinson-Klinik Ortenau, Wolfach, 77709, GermanyCorrespondence: Wolfgang H Jost, Parkinson-Klinik Ortenau, Kreuzbergstraße 12-16, Wolfach, 77709, Germany, Tel +49 7834 971-212, Fax +49 7834 971-340, Email w.jost@parkinson-klinik.deAbstract: COMT (catechol-O-methyltransferase) inhibitors are key therapeutic agents in the management of motor fluctuations (MF) in patients with Parkinson’s disease (PD). As levodopa/DDCI add-on therapy, their main benefit lies in increasing ON-time and reducing OFF-time for PD patients in the middle stages of the disease. Two of the three available COMT inhibitors, tolcapone and entacapone, have been approved for over two decades.Opicapone, a third-generation COMT inhibitor approved in 2016, was designed with the aim of overcoming specific challenges of the earlier generation compounds, specifically hepatotoxicity and short effect duration. This review aims at highlighting the specific properties and characteristics of opicapone, namely combining efficacy with good tolerability as demonstrated in the registration studies and since then confirmed under real-world conditions. Opicapone has been shown to be effective in patients with early, as well as late motor fluctuations. Whilst patients in the earlier Hoehn and Yahr stages benefit more than patients in later stages, the incidence of dyskinesia in patients with recent onset MF is around half that of patients with more established fluctuations. With the added advantage of a once-daily administration, this particular COMT inhibitor provides a simple, yet effective therapy for patients with Parkinson’s disease and MF.Keywords: Parkinson’s disease, motor fluctuations, opicapone, entacapone, COMT inhibitor, therapy